Use of photogrammetry to survey Iron Age rock art motifs in the Côa Valley: the Vermelhosa Rock 3 case study (Vila Nova de Foz Côa, Portugal) - Natália Botica; Luís Luís; Paulo Bernardes (Virtual Archaeology Review)
The Côa Valley, listed as a World Heritage site since 1998, presents over 1200 open-air engraved rock panels. The Archaeological Park of the Côa Valley has meticulously documented these rock art motifs, employing various techniques including direct tracing processes on the rocks, using both natural and artificial lighting. However, this intensive work is highly demanding, especially considering that many of the rocks are not easily accessible. In the context of the "Open Access Rock Art Repository" (RARAA) project, this paper presents a methodology for the three-dimensional (3D) survey of rocks with rock art motifs, as well as the subsequent production of orthophotos from the resulting 3D models, accomplished through photogrammetry. These orthophotos serve as the foundation for the vector drawing of the motifs. Remarkably, the level of detail captured in these records has shown that most of the motifs are visible and can be accurately represented through the orthophotos. This has significantly reduced the time required for field surveys. However, in certain cases where specific small areas of the panel are affected by challenging lighting conditions, further fieldwork is still necessary, analogous to the direct tracing process. Additionally, this study introduces an information system designed to integrate the vector graphics and the motifs characterisation data; this supports enhanced research in the area and promotes improved open access for potential reuse in new interpretations or integration into future projects. By creating highly detailed 3D models, the authors complement the two-dimensional drawings of the surfaces and ensure the digital preservation of both the rocks and the associated iconography. These records serve as highly detailed digital surrogates that facilitate the monitoring efforts of the rocks and motifs; they also guarantee the availability of valuable resources for future research and analysis, even if natural or deliberate changes occur.